Patterns of proton pump inhibitor utilization in gastroesophageal reflux disease and the effect of restrictions on reimbursement: a nationwide prescription database study. (September 2013) - Jonasson, Christian; Tvete, Ingunn F; Hatlebakk, Jan G.
Abstract: Objective. To assess the drug utilization patterns for proton pump inhibitors (PPIs) prescriptions dispensed in periods with and without restrictions on reimbursement in a public healthcare system. Material and methods. Data on all PPI prescriptions dispensed for gastroesophageal reflux disease (GERD) was retrieved from the Norwegian Prescription Database (NorPD) from 1 January 2004 to 31 January 2008. PPI utilization patterns were studied in new and current users of PPI in periods affected and not affected by a change in prescription policy. Results. The policy change resulted in 39% of esomeprazole patients discontinuing PPI therapy during a 12-month period while 23% discontinued PPI therapy during a period not affected by the policy change. The shift frequency to a different PPI was low, 5% and 7% respectively, during periods not affected by policy change. Despite a required shift in most esomeprazole patients, 64% still continued on esomeprazole. Among the 36% who shifted from esomeprazole to a different PPI, 25% subsequently shifted back to esomeprazole. In new PPI users, the proportion of esomeprazole users declined from 57% before to 20% after the introduction of the policy change. Conclusions. Despite GERD being a chronic disease in most patients, there was a high degree of alteration seen in the utilization patterns of PPIs. A high proportion discontinued PPI therapy indicating mild symptoms or remission. The switching between different PPIs was low indicating good efficacy and tolerability in most patients. The policy change was more effective in new PPI users compared with the mandated shift in ongoing esomeprazole users.